Muscle Strength of Upper Extremities and Trunk in Collegiate Throwing Players - Sookbat, Thanawat; Thodthong, Nuttanai; Prachayoon, Worasak; Choochuawsuwan, Jatsarit; Ingkatecha, Onwaree (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 2 (2019): April-June 2019DO - 10.14456/nujst.2019.13, 2019)
The overhead throwing, a complex movement skill used in sports, involved the series of linked movement of the body from legs through arm and hand with rotating each body segment to transfer velocity, momentum and energy in sequence such as tennis and volleyball serves, baseball pitching, javelin throw. The objectives of this study were to compare the strength of the upper extremities muscles of collegiate overhead throwing players, and healthy students who did not participate in these sports. The muscle strength of the dominant and non-dominant sides of the participants were included in the analysis and comparison. Sixty participants were divided into two groups; an experimental group consisted of 15 male players (age 20.47 + 1.19 years, bodyweight 69.57 + 8.25 kg, and height 168.47 + 24.73 cm) and 15 female players (age 19.87 + 0.99 years, bodyweight 61.20 + 12.16 kg, and height 162.27 + 5.28 cm). The other group was control group, consisted of 15 male non-players (average age 20.60 + 1.12 years, bodyweight 70.51 + 12.30 kg, and height 174.33 + 5.65 cm) and 15 female non-players (age 20.07 + 0.70 years, bodyweight 54.47 + 6.59 kg, and height 162.67 + 6.39 cm). Participants were tested and measured by the Upper Quarter Y-Balance test, in which the participants bore a weight on the testing arm at the center and reached in various directions. Paired and independent t-tests were used for comparing the differences of average composite scores between dominant and non-dominant, and between control and experimental groups respectively. The significant level was set at .05 (p < .05). The results revealed that there was no difference of the composite scores between dominant and non-dominant arms in all participants but there were significant differences of the composite scores on the dominant arm (p = .05) and non-dominant arm (p = 0.02) when comparing between control and experimental groups. It was concluded that there was no significant difference of the muscle strength of upper extremities and trunk, both dominant and non-dominant sides but the muscle strength of upper extremities and trunk of the overhead throwing players was lower than of the regular exercise group. It could be feedback information for coaches and players to improve training plans, skill development and injury risk reduction. Keywords: Overhead throwing, Muscle strength, Upper extremity, Trunk muscles